Neuregulin 1/ErbB signalling modulates hippocampal mGluRI-dependent LTD and object recognition memory. (April 2018) - Ledonne, Ada; Mango, Dalila; Latagliata, Emanuele Claudio; Chiacchierini, Giulia; Nobili, Annalisa; Nisticò, Robert; D'Amelio, Marcello; Puglisi-Allegra, Stefano; Mercuri, Nicola Biagio
Graphical abstract: Abstract: The neurotrophic factors neuregulins (NRGs) and their receptors, ErbB tyrosine kinases, regulate neurotransmission, synaptic plasticity and cognitive functions and their alterations have been associated to different neuropsychiatric disorders. Group 1 metabotropic glutamate receptors (mGluRI)-dependent mechanisms are also altered in animal models of neuropsychiatric diseases, especially mGluRI-induced glutamatergic long-term depression (mGluRI-LTD), a form of synaptic plasticity critically involved in learning and memory. Despite this evidence, a potential link between NRGs/ErbB signalling and mGluRI-LTD has never been considered. Here, we aimed to test the hypothesis that NRGs/ErbB signalling regulates mGluRI functions in the hippocampus, thus controlling CA1 pyramidal neurons excitability and synaptic plasticity as well as mGluRI-dependent behaviors. We investigated the functional interaction between NRG1/ErbB signalling and mGluRI in hippocampal CA1 pyramidal neurons, by analyzing the effect of a pharmacological modulation of NRG1/ErbB signalling on the excitation of pyramidal neurons and on the LTD at CA3-CA1 synapses induced by an mGluRI agonist. Furthermore, we verified the involvement of ErbB signalling in mGluRI-dependent learning processes, by evaluating the consequence of an intrahippocampal in vivo injection of a pan-ErbB inhibitor in the object recognition test in mice, a learning task dependent on hippocampal mGluRI. We found that NRG1 potentiates mGluRI-dependent functions on pyramidal neurons excitability and synaptic plasticity at CA3-CA1 synapses. Further, endogenous ErbB signalling per se regulates, through mGluRI, neuronal excitability and LTD in CA1 pyramidal neurons, since ErbB inhibition reduces mGluRI-induced neuronal excitation and mGluRI-LTD. In vivo intrahippocampal injection of the ErbB inhibitor, PD158780, impairs mGluRI-LTD at CA3-CA1 synapses and affects the exploratory behavior in the object recognition test. Thus, our results identify a key role for NRG1/ErbB signalling in the regulation of hippocampal mGluRI-dependent synaptic and cognitive functions, whose alteration might contribute to the pathogenesis of different brain diseases.